Evaluation of Latex sludge as a Phosphorus Source in Crop Production - Simi Sathyaseelan (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2004)
A detailed investigation entitled ‘Evaluation of latex sludge as a phosphorus source in crop production’ was carried out at College of Agriculture, Vellayani, with chilli (Capsicum annuum L.) as the test crop. Preliminary studies in both India and abroad had shown this waste product of latex concentrate industry to be a rich source of plant nutrients especially P. Initially the basic physico-chemical properties of this sludge material were estimated followed by an incubation study in which its P release pattern was compared with that of two conventional P sources -SSP and RP. Then pot culture experiments were undertaken to study its direct and residual effects on the growth and yield characters of chilli var. Jwalamukhi. Chemically, latex sludge is magnesium ammonium phosphate. Analytical studies revealed it to be near neutral (pH 6.49) in reaction which is mainly due to the pH buffering effect of its magnesium phosphate component. So, no significant variation in soil pH was observed both in the incubation study as well as in the pot culture experiments and in this respect it is comparable with the conventional P sources- SSP and RP. The total P content is 35.98 per cent grading it superior to rock phosphates now popular in market as commercial fertilizers. Of the total P, 13 per cent is water soluble and 36 per cent citrate soluble, together accounting for nearly half of the gross P content. The presence of both fractions gives latex sludge an added advantage over SSP and RP, in that it can provide both readily available and slowly available forms of P, making it suitable for a wide range of crops and soils. Another positive property of latex sludge is the presence of Mg (6.86 per cent) and N (6.05 per cent) in it. Mg has been found to be required by many plants in about the same quantities as P to increase their photosynthetic efficiency. The N is present in readily available form too ie., as ammonium phosphate. The presence of about five per cent organic C is another advantage as it enhances phosphate dissolution capacity of the material. In addition, it can supply minute quantities of K and Ca (less than one per cent). On the basis of its chemical profile, latex sludge can be considered more or less as a complete complex fertilizer. The greatest advantage is its ability to act as a slow release fertilizer, a property bestowed on it by the encapsulation of nutrients by rubber residues present in low concentration. The dynamics of important soil chemical properties on incubation with latex sludge (T1), SSP (T2) and RP (T3) were studied against a control (T4, soil alone) for a period of 120 days. These sources were applied to one kg soil taken in plastic containers, to provide P @ 40 kg ha-1 and the soil was maintained at field capacity. The superiority of latex sludge in increasing the soil organic C content was very much evident from the incubation study, even though there was an initial delay. From the 30th day onwards latex sludge was significantly superior to RP and SSP, the values gradually increasing to a maximum by the 75th day followed by a slow decline. The available N values were the highest for latex sludge applied soil throughout the incubation period except on the 105th day. From 30th to the 90th day these values were significantly superior to those for SSP and RP applied soils. The different P sources exerted significant influence on soil available P contents throughout the incubation period. On the 15th day, the water soluble phosphates of SSP maintained its superiority by recording a value significantly higher than that of all other sources. The next highest value was recorded by latex sludge and was significantly superior to RP. But from the 30th day onwards, P release from latex sludge and SSP became statistically comparable and significantly superior to that from RP. The uniform release pattern of both latex sludge and SSP continued till the 90th day and thereafter the three sources became on par in their P release capacities. The superior effect of latex sludge in maintaining a high soil available P till about 90th day is therefore very much evident and is mainly due to the presence of both water and citrate soluble P fractions in it. The available K levels in soil remained unaffected throughout the incubation period despite P application in different forms. The various P sources could produce significant variations in soil exchangeable Ca and Mg levels only towards the middle period of the incubation. In general, latex sludge was seen on par with RP in increasing soil exchangeable Ca but the Mg release pattern showed high inconsistency. The agronomic efficiency of latex sludge was evaluated by conducting pot culture experiments laid out in CRD with a main and a residue crop of chilli var. Jwalamukhi. The treatments included T1 (full P as LS), T2 (full P as SSP), T3 (full P as RP), T4 (¼ LS + ¾ SSP), T5 (½ LS + ½ SSP), T6 (¾ LS + ¼ SSP), T7 (¼ LS + ¾ RP), T8 (½ LS + ½ RP), T9 (¾ LS + ¼ RP), T10 (No P) and T11 (absolute control). Urea, muriate of potash and FYM were applied uniformly to all treatments except absolute control, as per Package of Practices Recommendations of Kerala Agricultural University. The P fertilizers were applied as per treatment schedule. The growth characters of chilli registered the maximum values when full P was given as SSP (T2). But, the effects were statistically on par with the combination treatment T8 (½ LS + ½ RP). Yield in general was favourably enhanced when latex sludge was applied along with RP. The highest yield was recorded by T7 (¼ LS + ¾ RP) but it was on par with T8 (½ LS + ½ RP). The economic analysis (benefit-cost ratio) also showed the same trend of yield. The quality traits of chilli also testified the suitability of latex sludge as an alternate P source. The treatment combination T8 (½ LS + ½ RP) registered values which were either the highest or on par with the highest. The plant uptake of nutrients, a major yield contributing factor, also showed trends in favour of latex sludge. The uptake of N, P, K, Ca and Mg which were significantly influenced by the treatments were the highest or on par with the highest for the combination treatment, T8. Chemical analysis of soil upon crop harvest indicated that the combination treatment T8 (½ LS + ½ RP) could maintain higher levels of available N, P and exchangeable Mg. Full P as latex sludge (T1) recorded the highest organic C content and was significantly higher than all other treatments. The residual effects of the treatments were studied by raising another crop of same variety of chilli in the same pots using the same soil following all the cultural operations as for the main crop except P addition. The highest residual effect of P was exhibited by the combination treatment T8 (½ LS + ½ RP) manifested by recording the highest fruit yield and thereby the highest returns. The high residual effect of T8 (½ LS + ½ RP) was also evident from its highest P uptake indicating adequate P availability inspite of its lack of application to the current crop. Moreover, the uptake of other nutrients was either the highest or on par with the highest value for the same treatment (T8). The present investigation, therefore, undoubtedly proves that latex sludge can be used as an alternate and cheap source of P in crop production. The combination treatment T8 (½ LS + ½ RP) emerges superior on the basis of its direct and residual effects on growth, yield and quality characters of chilli. Economic analysis substantiates this further. Moreover, use of this apparently ecofriendly material in crop production will be a boon in terms of its disposal also.